THE SIGNIFICANCE OF TEACHING ENGLISH TO THE STUDENTS OF ECONOMICS - Juraeva Zarinakhon Bakhodir kizi (Western European Studies, 2024)
The article discusses various features of the process of teaching English to first course-students of Economics major. It shows the role of foreign language skills in the context of globalization and internationalization of economic relations and substantiates the importance of quality of English language proficiency not only in terms of the needs of the students, but also from the standpoint of improving the corporate culture of the organization, where economist will work in the future.
Keywords: English; teaching languages; methods; economics